2023
DOI: 10.1371/journal.pone.0266207
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rat forelimb vascularized composite allograft (VCA) perfusion protocol

Abstract: Vascularized composite allografts (VCAs) refer to en bloc heterogenous tissue that is transplanted to restore form and function after amputation or tissue loss. Rat limb VCA has emerged as a robust translational model to study the pathophysiology of these transplants. However, these models have predominately focused on hindlimb VCAs which does not translate anatomically to upper extremity transplantation, whereas the majority of clinical VCAs are upper extremity and hand transplants. This work details our opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Furthermore, an optimal flow rate/pattern has not yet been defined, as it can vary depending on the perfusion solution, tissue, and characteristics of the perfusion system itself. 11 , 32 , 33 However, our HMP model shows that it is possible to achieve complete distribution of KPS-1 solution without significantly increasing edema in rat hindlimb VCAs. Therefore, there is potential to further improve this system and its storage outcomes through the addition of cell death inhibitors and other therapeutic agents.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Furthermore, an optimal flow rate/pattern has not yet been defined, as it can vary depending on the perfusion solution, tissue, and characteristics of the perfusion system itself. 11 , 32 , 33 However, our HMP model shows that it is possible to achieve complete distribution of KPS-1 solution without significantly increasing edema in rat hindlimb VCAs. Therefore, there is potential to further improve this system and its storage outcomes through the addition of cell death inhibitors and other therapeutic agents.…”
Section: Discussionmentioning
confidence: 83%
“…Our study showed insignificant amounts of edema, apoptosis, and necrosis using KPS-1 even after prolonged storage at 24 h. Numerous other studies have shown much shorter storage times and greater amounts of apoptosis, necrosis, and edema using alternative perfusion solutions such as BSA- or DMEM-based solutions. 11,32,33 Although there is currently no universally accepted perfusion solution for VCA transplantation, our study indicates there is the potential for KPS-1 to fill this gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, for clinical applications, the perfusate should be micro-filtrated and discarded, and should not be recirculated. We used biochemical metrics such as potassium, lactate, pH, and oxygen consumption by translation from other VCA models [31,32,43]. These metabolic outcomes have been shown to be relevant in solid organ preservation [35,44], but other parameters may be suitable for fasciocutaneous flaps.…”
Section: Discussionmentioning
confidence: 99%